Breeding scheme based on community-based participatory analysis of local breeding practices, objectives and constraints for goats around Dire Dawa, Ethiopia - Gebreyesus, G.; Haile, Aynalem; Dessie, Tadelle (2013)
This study was conducted in the rural kebeles around Dire Dawa for designing a simple, yet, feasible breeding scheme in the context of community-based management of animal genetic resources. Range of participatory rural appraisal tools, including focal group discussions and participatory mappings, were employed to study the local community’s Indigenous knowledge and practices in managing the goat gene pool. The breeding objective and local trait preferences were defined in a participatory manner through own-flock ranking experiments. The community generally practices selective pure breeding where by the own flock and flocks in the neighbourhood were the units of selection for bucks. There are social regulations in the community against sale of breeding does outside the community while encouraging communal use of outstanding breeding males. Goats are kept for multifaceted purposes ranging from products like milk, meat and live-sale to functions in socio-cultural, financial and ritual state of affairs. The breeding objective is to ensure improved milk production, through increased daily yield per doe and increased fertility per flock, and increased net income per flock, through increased number of marketable animals. Traditional criteria such as conformation, behaviour and adaptation were as important as most “production” traits in selecting breeding animals. The breeding goal traits considered were, accordingly, milk production, conformation and reproductive traits. Based on these findings, village breeding schemes, where-by flocks and breeding groups in a village are taken as focal points, is recommended as way forward in genetic improvement. The framework for a feasible implementation of such genetic improvement scheme is outlined based on the rationale of utilizing available social regulations, indigenous knowledge and traditional systems of breeding as well as future market prospects.